Barium-induced toxic anterior segment syndrome. Issue 3 (May 2023) - Matsushita, Kenji; Kawashima, Rumi; Hashida, Noriyasu; Hamano, Yuki; Harada, Kazuo; Higashisaka, Kazuma; Baba, Koichi; Sato, Shigeru; Huang, Weiran; Matsumoto, Hiroshi; Hamanaka, Teruhiko; Quantock, Andrew J.; et al.
Toxic anterior segment syndrome (TASS) is a rapid-onset inflammation of the eye following uneventful ocular surgery. We report a case of TASS following Baerveldt glaucoma implant (BGI) surgery. Inductively coupled plasma-mass spectrometry (ICP-MS) identified barium in the eye and in the eluate from the bleb of the BGI. We attribute TASS in our patient to the dissolution of barium from the BGI and its entry into the eye, where it causes severe inflammation.